Ekonomi Dalam Kajian Al-Qur'an - Muhazir, Muhazir (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2021)
Economics in general is knowledge and investigation of the principles of property in Islam, distribution, and the use of goods and wealth in the context of the Quran. The study of assets in the Economy is a human desire in an effort to fulfill their needs. In this paper, we will discuss the analysis of Quran in chapter Al-Furqan verse 67 which intersects directly with the verse on economics, especially economically in the distribution of assets and the method used in this paper is the Maudu'i. This research is a literature review (library research) with primary data in the form of QS. Al-Furqan Verse 67, the approach used is the hermeneutic approach by examining the words contained in the verse. The results showed that there was a correlation between extravagant and vicious characteristics, because extravagant nature tends not to be able to control the property acquired proportionally which is able to lead to extravagant.